2005
DOI: 10.1103/physrevlett.94.065302
|View full text |Cite
|
Sign up to set email alerts
|

Kolmogorov Spectrum of Superfluid Turbulence: Numerical Analysis of the Gross-Pitaevskii Equation with a Small-Scale Dissipation

Abstract: The energy spectrum of superfluid turbulence is studied numerically by solving the GrossPitaevskii equation. We introduce the dissipation term which works only in the scale smaller than the healing length, to remove short wavelength excitations which may hinder the cascade process of quantized vortices in the inertial range. The obtained energy spectrum is consistent with the Kolmogorov law.PACS numbers: 67.40. Vs, 47.37.+q, 67.40.Hf The physics of quantized vortices in liquid 4 He is one of the most import… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
234
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(252 citation statements)
references
References 20 publications
17
234
0
Order By: Relevance
“…Then, the incompressible kinetic energy spectrum was found to exhibit the Kolmogorov −5/3 power law in a limited time period. After this study, Parker et al also confirmed the Kolmogorov law in QT in a rotating system [125], and Kobayashi et al introduced a phenomenological dissipation term into the GP equation and obtained the Kolmogorov law [126]. Figures 23 (a) and (b) are the vortex configuration and the incompressible kinetic energy spectrum in Ref.…”
Section: Vortex Turbulence Of Single-component Becs In 3d Systemsmentioning
confidence: 75%
See 2 more Smart Citations
“…Then, the incompressible kinetic energy spectrum was found to exhibit the Kolmogorov −5/3 power law in a limited time period. After this study, Parker et al also confirmed the Kolmogorov law in QT in a rotating system [125], and Kobayashi et al introduced a phenomenological dissipation term into the GP equation and obtained the Kolmogorov law [126]. Figures 23 (a) and (b) are the vortex configuration and the incompressible kinetic energy spectrum in Ref.…”
Section: Vortex Turbulence Of Single-component Becs In 3d Systemsmentioning
confidence: 75%
“…Figures 23 (a) and (b) are the vortex configuration and the incompressible kinetic energy spectrum in Ref. [126], where the decaying QT is generated by the initial state with random phase and the Kolmogorov law is confirmed. Furthermore, Kobayashi et al generated the stationary steady state QT using the dissipative GP equation and obtained the Kolmogorov law [127,128].…”
Section: Vortex Turbulence Of Single-component Becs In 3d Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Araki et al made a vortex tangle arising from Taylor-Green vortices and obtained an energy spectrum consistent with the Kolmogorov law. The third used the modified GP model by Kobayashi and Tsubota [44,45].…”
Section: Energy Spectra and Dissipation At Zero Temperaturementioning
confidence: 99%
“…In this work, we limit ourselves to the numerical solutions of the time-reversal invariant GP equation, valid for temperatures as close as possible to absolute zero, but we recognize that in order to make a direct comparison with actual experiments, being these at finite temperature, one must take into account dissipative effects. There are already efforts along these lines 24,25,26,27,28,29,30 including the effects of the thermal cloud that surrounds a confined BEC. True stationary states, of course, are found in those cases…”
Section: Introductionmentioning
confidence: 99%